Acute effects of singing on cardiovascular biomarkers - Somayaji, Kamila; Frenkel, Mogen; Tabaza, Luai; Visotcky, Alexis; Ruck, Tanya Kruse; Ofori, Ernest Kwesi; Widlansky, Michael E.; Kulinski, Jacquelyn (Frontiers in Cardiovascular Medicine, 2022)
Background Singing is a physical activity involving components of the vagal nerves manifested as changes in cardiac autonomic regulation. Aims: The aim of this pilot study is to investigate the acute effects of singing on biomarkers of cardiovascular health. Methods: Adult subjects were recruited from cardiology clinics to participate in a single 90-minute study visit. Vascular function was measured at the fingertips with peripheral arterial tonometry (PAT) before and after singing to a 14-minute video led by a voice expert. Heart rate variability (HRV) was measured with a chest strap sensor at baseline, during, and after singing. PAT measurements were expressed as reactive hyperemia index (RHI) and Framingham reactive hyperemia index (fRHI). Measures of HRV included root mean square of successive RR interval differences (RMSSD) and standard deviation of NN (or RR) intervals (SDNN). Results: Sixty subjects completed the study (68% female, mean age 61 ±13 years, mean BMI 32 ±8). There was a significant increase in fRHI (1.88 ±0.14 to 2.10 ±0.14, p=0.02) after singing with no significant change in the RHI (1.99±0.10 to 2.12±0.09, p=0.22). There was a reduction in HRV during singing (compared to baseline) (RMSSD: 42.0±5 to 32.6±4, p= 0.004 and SDNN: 54±4 to 33.5±3, p=0.009). HRV measures trended back towards baseline after singing. Conclusions: A short duration of singing improved vascular function acutely. Improvements were more substantial in subjects with abnormal baseline endothelial function. HRV patterns were similar to that of light-intensity exercise. Future studies should confirm favorable vascular adaptation to more sustained singing interventions.